Z dziejów prasy wielkopolskiej XIX -XX wieku, praca zbiorowa pod red. Marcelego Kosmana, t. 1-4, UAM, Poznań 1994, 1995, 1997, 1998, s. 189, 163, 213, 195 - Kochańska, Barbara (Biuletyn Historii Wychowania, 1998)
Z dziejów prasy wielkopolskiej XIX -XX wieku, praca zbiorowa pod red. Marcelego Kosmana, t. 1-4, UAM, Poznań 1994, 1995, 1997, 1998, s. 189, 163, 213, 195